Marketing Communication Strategy on Instagram of Asa Cerra's Probiotic Drink - Maulana, Evinka Aisha; Wulansari, Amilia (Journal of Consumer Studies and Applied Marketing, 2024)
The growth of Indonesia's probiotic, health, and wellness industry has compelled companies in this sector to adopt effective marketing communication strategies to address customer needs and preferences. Companies are increasingly promoting the value of their products by highlighting their benefits and ingredients. Asa Cerra, a new company preparing to launch its probiotic product "Nata de Whey," recognizes the importance of understanding the customer profile to effectively tailor its value proposition and marketing strategies. This research aims to identify the characteristics of Asa Cerra's target customers, employing the AIDA Marketing Funnel framework. The research includes an internal analysis of Asa Cerra's capabilities and resources and an external analysis using PESTLE and Porter's Five Forces frameworks. It also involves assessing customer insights and competitive dynamics. Qualitative research is conducted through in-depth interviews with 7 Asa Cerra customers, one probiotic expert, and one marketing expert. The findings indicate that Asa Cerra's customers are health-conscious and well-informed about probiotics. They seek information from various sources, including scientific journals, social media, experts, and personal networks. They also maintain an open-minded approach to new developments. Asa Cerra will implement a multi-faceted marketing strategy to engage effectively with these customers. This includes raising awareness through Instagram content and campaigns that promote the benefits of probiotics and "Nata de Whey," generating interest by sharing product details and testimonials, building desire by highlighting unique benefits, pricing, availability, and community aspects, and driving action with a seamless e-commerce platform and excellent after-sales service. This comprehensive approach will ensure that Asa Cerra's marketing communication strategy aligns with customer expectations and supports successful product adoption.